RELASI KOEKSISTENSIAL SAPAAN KEBERABATAN BAHASA TABA - Ibrahim, Gufran A.; Maricar, Farida; Muhamad, Hujaefa Hi (Linguistik Indonesia, 2024)
Greetings in different languages around the world reflect unique kinship dynamics within both nuclear and extended families. The Watam, also known as Marangis, a variant of the Ramu spoken by approximately 590 native speakers (Lewis, 2009: 623) in Papua New Guinea, employs two distinct kinship vocabularies in two sets of reciprocal relations to articulate greetings between aunt and nephew (namong~namkwae), uncle and niece (amuk~akwae), and uncle and nephew (aem~namong) (Foley, 2009:131--149). Building upon the insights discovered from the kinship greeting system in the Watam, the study of the Taba (Bowden, 2001), also referred to as East Makian (Lewis, 2009) spoken in North Maluku was investigated. The objective is to identify and elucidate the greeting lexicon in the Taba that signifies kinship relations. Employing a qualitative methodology (Miles and Huberman, 1992), the data collection techniques encompassed interviews, expert consultations, and recordings (Sudaryanto, 1993). Data analysis and interpretation drew upon two complementary theoretical frameworks: anthropological theories of kinship (Foley, 2009) and morphological theories (Nida, 1949). Findings reveal that the Taba encompasses six distinct kinship greetings related to marital relations. These greetings denote coexistential relations between parents and children, spouses, siblings, uncles and nephews, aunts and nephews, and grandparents and grandchildren. Each of these relations is characterized by the utilization of six unique morphemes: ko, doma, mota, hoh, mom, and bum. Additionally, the repertoire of coexistential relational greetings can be expanded through the incorporation of relevant unique morphemes. Collectively, these six greetings delineate relationships within both the nuclear and extended family spheres.